A new species of Physokermes Targioni Tozzetti (Hemiptera: Coccoidea: Coccidae) from Greece - Kozár, Ferenc; Gounari, Sofia; Hodgson, Chris; Fetyk, Kinga; Goras, G. (Zootaxa, 2012)
During surveys of scale insects in Greece, a new species of Physokermes (Coccidae: Coccoidea: Hemiptera), P. hellenicus Kozár & Gounari, sp. n., was collected on the conifer Abies cephalonica (Pinaceae). The adult male, adult female, third-instar female, second-instar male and female, and the first-instar nymphs are described. This is the first time a third-instar female has been found in the Kermesidae. A key is provided to identify the adult females of western Palaearctic species of Physokermes.